XANTHINE OXIDASE INHIBITORY, ANTIHYPERURICEMIC, ANTI-INFLAMMATORY, ANTINOCICEPTIVE ACTIVITY OF Î±-LIPOIC ACID IN GOUTY ARTHRITIS MODEL - Hameed, Basim Jasim; Ramadhan, Usama Hamid (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The current study was carried out to investigate the xanthine oxidase inhibitory, antihyperuricemic, anti-inflammatory, and antinociception activity of Î±-lipoic acid (LA) in gouty model of rats. Methods: Enzyme assay was done using bovine milk xanthine oxidase (XO). The XO inhibitory activity in vitro was performed using different doses of Î±-LA, and the degree of XO inhibition was expressed as IC50. The antihyperuricemic activity of Î±-LA was tested in the potassium oxonate-induced hyperuricemic rats for 7 consecutive days of oral treatment of 10, 25, and 50 mg/kg doses. The anti-inflammatory activity was achieved through monosodium urate crystal-induced inflammation hind paw model in mice. The antinociception effects of Î±-LA were explored using both of writhings induced by acetic acid test and hot plate test. Results: The study results revealed that the Î±-LA has a potent activity of XO inhibition with IC50 = 2.93 Î¼g/mL. Furthermore, these results showed that all doses of Î±-LA were able to significant reduce of each the following: Serum uric acid levels in the hyperuricemic rats, hind paw thickness of mice at all periods of time assessment, and writhings number in the acetic acid-induced writhing test, while, the same doses significantly increased the reaction latency in mice at hot plate test. Conclusion: The Î±-LA showed a significant effect on the evaluated models, and therefore it may be a promising agent for the treatment of gout since it possesses XO inhibitory, antihyperuricemic, anti-inflammatory, and antinociception activity. Â 